P-017 A FRAMEWORK FOR MULTIDISCIPLINARY TEAM MANAGEMENT OF ABDOMINAL WALL RECONSTRUCTION. (13th October 2022) - Wei, R; Gilmore, K; Findlay, J; Sanders, D; Pawlak, M; Bunting, D; Arain, A
Abstract: Aim: Incisional hernias are common and can significantly impact a patient's quality of life. Traditionally, abdominal wall reconstruction (AWR) has been performed by general surgeons, or those with special interest, often working in isolation. However, there is increasing awareness of pre-optimisation, risk stratification, enhanced training, and personalising treatment using a wide range of techniques. Methods & Results: For complex and higher-risk procedures, Multidisciplinary team (MDT) management is considered the standard of care for optimising outcomes. The lack of standardised protocols and clear evidence in AWR means that surgical management can vary greatly. This makes the MDT process even more important due to the complexity of the decision-making involved. We describe a successful MDT process for complex abdominal wall reconstruction at a tertiary referral centre. Patients are reviewed at weekly AWR meetings with a multidisciplinary team, which includes consultants, advanced clinical practitioners and trainees. This is an opportunity for objective risk stratification, radiological review and assessment of the patient's goals before preoptimization and operative planning. Prospective data is collected on all patients to allow for quality improvement and service development. Conclusion: MDT management of abdominal wall hernia is gaining popularity but remains poorly established in most regions. The involvement of surgical colleagues and other specialists is crucial in developing this growing field of surgery. We hope to expand our team to include Radiologists and Nutritionists, with the possibility of extending to regional networks, as we continue to explore new techniques and methods in managing complex abdominal wall hernias.